THE QUESTION OF THE COMPARATIVE STUDY OF THE LEADING IMAGES IN THE VARIANTS OF THE SINGLE AXMAD EPIC (Modern education and development, 2025)
This article deals as much as possible with the comparative study of the leading characters in the variants of the single Axmat epics.